2020
DOI: 10.1103/physrevlett.124.166601
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Anomalous Hall Ferromagnetism in Twisted Bilayer Graphene

Abstract: We use a lowest Landau level model to study the recent observation of an anomalous Hall effect in twisted bilayer graphene. This effective model is rooted in the occurrence of Chern bands which arise due to the coupling between the graphene device and its encapsulating substrate. Our model exhibits a phase transition from a spin-valley polarized insulator to a partial or fully valley unpolarized metal as the bandwidth is increased relative to the interaction strength, consistent with experimental observations.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
294
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(309 citation statements)
references
References 91 publications
12
294
0
3
Order By: Relevance
“…For isolated TBG, the point group symmetry is D 6 which allows a longitudinal response only, so the induced magnetization will be parallel to the direction of the current as shown in Table I. However, the substrate can strongly affect the properties of TBGs [26][27][28][29]. Effects of a rotationally-aligned hBN substrate on the nearest graphene layer are to break the sublattice symmetry and to induce strain so that the symmetry of the full TBG stack is reduced to C 1 .…”
Section: Discussionmentioning
confidence: 99%
“…For isolated TBG, the point group symmetry is D 6 which allows a longitudinal response only, so the induced magnetization will be parallel to the direction of the current as shown in Table I. However, the substrate can strongly affect the properties of TBGs [26][27][28][29]. Effects of a rotationally-aligned hBN substrate on the nearest graphene layer are to break the sublattice symmetry and to induce strain so that the symmetry of the full TBG stack is reduced to C 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In Refs. [27,28], it was found that a non-zero sublattice splitting on one side of magic-angle tBLG gaps out all Dirac cones of the Moiré Hamiltonian. Because the two Dirac cones in a single-valley Moiré Hamiltonian, shown in Fig.…”
Section: Magic-angle Twisted Bilayer Graphene Aligned With Hbnmentioning
confidence: 99%
“…For instance in tBLG, the flat bands have non-trivial fragile topology protected by the space group symmetries [21][22][23][24]. In devices which have isolated flat bands, one generally finds broad parameter regimes where these bands have non-zero Chern number [19,20,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Most saliently, we provide microscopic evidence that high temperature fractional Chern insulators can form in twisted bilayer graphene aligned with hexagonal boron nitride.Setup. Motived by the recent discoveries [11][12][13]15] along with theoretical predictions [16,21] of spin and valley polarized insulators at integer fillings in various Moiré bands, we consider electrons with polarized spin arXiv:1912.04907v1 [cond-mat.mes-hall]…”
mentioning
confidence: 99%